Study on exploring Scimp in peripheral blood as a biodiagnostic marker for MAFLD-related cirrhosis based on animal experiments - CHEN Hongwei, ZHU Ting, LIU Yan, HOU Yanqiang, FAN Guangjian (Zhenduanxue lilun yu shijian)
Objective This study aims to identify biodiagnostic markers for the progression of metabolic-associated fatty liver disease (MAFLD) to cirrhosis, providing evidence for early diagnosis and treatment of cirrhosis. Methods The experiment utilized healthy male Sprague Dawley (SD) rats, which were randomly divided into a normal control (NC) group of 15 rats, a high-fat diet (HFD) group of 15 rats, and a liver fibrosis (LF) group of 15 rats. Rats in the NC group were fed a normal diet, those in the HFD group received continuous high-fat diet to induce fatty liver and mild liver fibrosis, and those in the LF group were fed a high-fat diet and injected with carbon tetrachloride to induce cirrhosis. After 41 weeks of feeding, blood and liver tissues were collected from rats. Liver tissues were stained with hematoxylin and eosin (HE), Oil Red O, and Sirius red to evaluate liver morphology, fat infiltration, and liver fibrosis. Differentially expressed genes in blood samples were screened using mRNA sequencing technology, and the expression of sequencing-screened differentially expressed genes was validated by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR). Additionally, blood samples from 10 human subjects each in the NC, MAFLD, and cirrhosis groups were collected from January to February 2025 at Songjiang Hospital Affiliated to Shanghai Jiao Tong University School of Medicine to validate the mRNA expression of screened differentially expressed genes. Results The mRNA sequencing of peripheral blood cells in rats identified 17 differentially expressed genes, including Rab3ip, Gprasp2, Emid1, Hbq1b, Scimp,Wipf3, Scrn1, Sez6, Bglap, Bhlhb9, Ranbp10, Ubd, Plekhb1, Nup210l, Gp1bb, Cpne8, and Oscar. The RT-qPCR validation results showed that the mRNA expression levels of the Scimp gene in the NC group, HFD group, and LF group exhibited an increasing trend in sequence, which was consistent with the sequencing results. Pairwise comparisons between groups showed statistically significant differences (P < 0.01). The RT-qPCR validation results of human peripheral blood cells were consistent with the mRNA sequencing and RT-qPCR validation expression trends of the Scimp gene in rat peripheral blood. Scimp showed the same expression differences among NC, MAFLD, and cirrhosis patients (P < 0.05). Conclusions The mRNA expression level of the Scimp gene in peripheral blood cells can serve as a potential non-invasive biodiagnostic marker for early-stage cirrhosis.